Counting and subitizing skills in children with Down syndrome and autism spectrum disorder - Kobayashi, Waka; Koizumi, Manami; Kojima, Michio (Frontiers in Education, 2025)
IntroductionPrevious studies have shown that the disability characteristics of Down syndrome (DS) and autism spectrum disorder (ASD) may affect the development of counting and subitizing skills.MethodsIn this study, two tasks were conducted to examine the development of counting and subitizing skills in children with intellectual disabilities, including DS and ASD, and the results were compared with the performance of typically developing (TD) children.ResultsThe maximum countable number attained by children with DS was considerably lower than that of children with ASD. However, the subitizing range of children with DS was not substantially different from that of children with ASD or TD children, suggesting that the subitizing abilities of children with DS may be relatively well-developed. Although it was predicted that children with ASD would exhibit characteristic counting strategies such as frequent pointing and a smaller subitizing range, the results were not in line with the hypotheses.DiscussionThese results indicate that children with intellectual disabilities may show more specific developmental trajectories related to counting and subitizing based on disability type (DS and ASD). Moreover, children with DS may exhibit developmental variation between the two processes, as they are often able to subitize quantities consistent with their mental age yet demonstrate difficulty when counting a higher number of objects than the subitizing range.